„Unter dem Banner des Asianismus“:: Transnationale Dimensionen des japanischen Asianismus-Diskurses der Taishō-Zeit (1912–1926) - Weber, Torsten (Comparativ, 2008)
“Under the banner of Asianism”: transnational dimensions of Japanese Asianism discourse during the Taishō period (1912–1926) This article investigates the background and dynamics of the emergence and establishment of Asianism (Ajiashugi) as a contested key concept in mainstream political discourse in Japan during the 1910s and 1920s. Mainly focusing on the influence of Chinese and “Western” conceptions of Asianism on the debate in Japan, it analyses the Japanese “embrace of Asia” during the Taishō period (1912–1926) in a transnational politico-intellectual context. Initially, not only claims for Asian unity were largely rejected but Japanese “Asianity” as such was disputed by a majority of public opinion leaders. After the First World War, however, Japanese intellectuals increasingly began to embrace the idea of Asia and to propose Asianism as a political principle in opposition, or complementary to, the predominant doctrines of the time, such as nationalism, internationalism, or imperialism. While the self-affirmative call for an “Asia for the Asians” appealed to participants in this debate beyond national and ideological borders, the mere adoption of “Western” Orientalist rhetoric by Japanese and Chinese proponents of Asianism obstructed a full-scale conceptual emancipation from “the West”.